2013
DOI: 10.1111/cdev.12102
|View full text |Cite
|
Sign up to set email alerts
|

Why Are Chinese Mothers More Controlling Than American Mothers? “My Child Is My Report Card”

Abstract: Chinese parents exert more control over children than do American parents. The current research examined whether this is due in part to Chinese parents' feelings of worth being more contingent on children's performance. Twice over a year, 215 mothers and children (mean age = 12.86 years) in China and the United States (European and African Americans) reported on psychologically controlling parenting. Mothers also indicated the extent to which their worth is contingent on children's performance. Psychologically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
199
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(231 citation statements)
references
References 93 publications
12
199
3
Order By: Relevance
“…The mean of all items was taken, with higher numbers indicating greater psychological control. The measure has proved valid and appropriate among Chinese adolescents (e.g., Ng et al, 2014). The confirmatory factor analysis indicated that construct validity of the instrument was acceptable in the present study, χ 2 = 622.81, df = 132, p < 0.001, RMSEA = 0.08, CFI = 0.89, TLI = 0.88.…”
Section: Psychological Controlsupporting
confidence: 51%
See 1 more Smart Citation
“…The mean of all items was taken, with higher numbers indicating greater psychological control. The measure has proved valid and appropriate among Chinese adolescents (e.g., Ng et al, 2014). The confirmatory factor analysis indicated that construct validity of the instrument was acceptable in the present study, χ 2 = 622.81, df = 132, p < 0.001, RMSEA = 0.08, CFI = 0.89, TLI = 0.88.…”
Section: Psychological Controlsupporting
confidence: 51%
“…Compared with Western counterparts, Chinese parents use more psychological controlling and less autonomy-supportive practices (Ng et al, 2014;Doan et al, 2017). In addition, Chinese parents and students might interpret parental psychological control differently from Western counterparts, treating it as the expression of love and discipline while not an intrusion upon children's sense of self (Wang et al, 2007;Soenens et al, 2012).…”
Section: Parental Psychological Control Autonomy Support and Academmentioning
confidence: 99%
“…Second, because Chinese parents have high expectations from their children (Li, 2003;Ng, Pomerantz, & Lam, 2007), they engage more frequently in their learning (Huntsinger et al, 1997;Ng, Pomerantz, & Deng, 2014;Pan et al, 2006). For example, Huntsinger et al (1997) showed that Chinese-American parents spend more time on their children's homework, structure their children's time to a greater degree, and show more encouragement for mathematics-related activities than do their European-American counterparts.…”
mentioning
confidence: 99%
“…For example, Huntsinger et al (1997) showed that Chinese-American parents spend more time on their children's homework, structure their children's time to a greater degree, and show more encouragement for mathematics-related activities than do their European-American counterparts. In addition, the widely held belief among Chinese families is that a child achieves for his/her family (Ng et al, 2014). A child's performance reflects on the family; therefore, parents have one more reason to help their children learn the subject matter (Huntsinger & Jose, 2009).…”
mentioning
confidence: 99%
“…However, two possible explanations include school-related stress and school-day lengths. First, Chinese students tend to feel greater stress from academics than other students (Sun, Dunne, & Hou, 2012;Ng, Pomerantz, & Deng, 2014). Second, there was disparity in the American and Chinese high school schedules for the participating schools.…”
Section: Discussionmentioning
confidence: 99%